Food and nutrition insecurity: a marker of vulnerability to asthma symptoms. Issue 1 (21st January 2013) - Ribeiro-Silva, Rita de Cássia; Oliveira-Assis, Ana Marlúcia; Junqueira, Samuel Badaró; Fiaccone, Rosemeire Leovigildo; dos Santos, Sandra Maria Chaves; Barreto, Maurício Lima; de Jesus Pinto, Elizabete; da Silva, Luce Alves; Rodrigues, Laura Cunha; Alcantara-Neves, Neuza Maria
Abstract: Objective: To evaluate the association between food and nutrition insecurity and asthma in children from Latin America. Design: Cross-sectional study. Setting: São Francisco do Conde, Bahia, north-eastern Brazil. Subjects: The study included 1307 children aged 6–12 years from public elementary schools. Asthma symptoms were collected using a questionnaire that was translated and adapted from the International Study of Asthma and Allergies in Childhood, phase III. The diagnosis of asthma was determined based on reports of wheezing in the previous 12 months. The Brazilian Food Insecurity Scale was used to identify food insecurity. We also obtained demographic, socio-economic and anthropometric information for each participant. We used multivariate logistic regression analyses to assess the associations of interest. Results: Of the children surveyed, 10·4 % had a history of wheezing and 64·5 % had some degree of food and nutrition insecurity. We found a positive dose–response relationship and statistically significant associations of asthma with moderate (OR = 1·71, 95 % CI 1·01, 2·89) and severe (OR = 2·51, 95 % CI 1·28, 4·93) food and nutrition insecurity. Conclusions: The results show that moderate and severe food and nutrition insecurity are markers of vulnerability to wheezing. It is important to note that the results of studies in this field have potential implications for social policies that promote food security. Further studies to identify the mechanisms involved in the relationship between food and nutrition insecurity and asthma are needed.